1988
DOI: 10.1002/pen.760282202
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the nature and content of antioxidant and antioxidant synergist in polyethylene and crosslinked polyethylene used in cables

Abstract: It is shown that polyethylene and crossllnked polyethylene resins used for cable applications contain an antioxidant synergist in addition to an antioxidant. Their nature and content have been determined by a combination of ultraviolet and Fourier transform infrared spectroscopy and neutron activation analysis measurements. The results thus obtained suggest that part of the antioxidant compound is grafted to polymer chains during crosslinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Based on the kinetic studies, it was found that under some conditions the acid catalyzed process occurred at a faster rate than the thermal process. This in combination with the known intermediacy of various sulfur acids in the functioning of BOCES as a secondary antioxidant motivated the current study on transformations that occur in this important system. As in previous studies, dodecane was selected as the reaction medium of choice to enable utilization of a variety of analytical techniques while serving as a chemically relevant model for polyethylene used in XLPE.…”
Section: Introductionmentioning
confidence: 98%
“…Based on the kinetic studies, it was found that under some conditions the acid catalyzed process occurred at a faster rate than the thermal process. This in combination with the known intermediacy of various sulfur acids in the functioning of BOCES as a secondary antioxidant motivated the current study on transformations that occur in this important system. As in previous studies, dodecane was selected as the reaction medium of choice to enable utilization of a variety of analytical techniques while serving as a chemically relevant model for polyethylene used in XLPE.…”
Section: Introductionmentioning
confidence: 98%
“…The higher sulfate content in UC 4201 and in all cables corresponds to the presence of a sulfur-containing antioxidant[4]. Note that part of the very high sulfate content in furnace-black-loaded shield may Chloride content in the various samples.…”
mentioning
confidence: 94%